A comparative study of Odonata (Insecta) assemblages along an altitudinal gradient in the sierra de Coalcomán Mountains, Michoacán, Mexico - Rodolfo Novelo-Gutiérrez; JOSE ANTONIO GOMEZ ANAYA (Biodiversity Conservation, 2009)
Odonate diversity in the Coalcomán Mountain Range (CMR), Michoacán State, Mexico, was surveyed, and samplings were made during 2 years in eight streams along an altitudinal gradient. Presence?absence data were analyzed using non-parametric and parametric methods. Beta and gamma diversities were estimated using Whittaker?s and Lande?s formulae, respectively. A total of 2,526 adults and 489 larvae were captured, yielding 116 species (c diversity), 44 genera and 9 families. Five new species were dis- covered. The genus Argia was the most important contributor to Zygoptera diversity and total richness (y diversity), yielding 40.4 and 14.7%, respectively. The non-parametric estimator Chao2 provided the closest theoretical estimate of species richness, and Clench?s model fit the data well (R2 ranged from 99.44 to 99.99) to explain a high proportion of the variance (98.8). We conclude that beta diversity is important at the landscape scale, supporting the hypothesis that Mexico is a beta diverse country. Our results triple the number of known species of Odonata for Michoacán. Given the considerable richness of odonates at local and landscape scales, our results support the proposal of the Coalcomán Mountain Range as a priority area for conservation and related research.